Detection and analysis method for broken cloth

The appropriate carbonization temperature is determined through detection and analysis methods, and the cloth-broken samples are subjected to low-temperature shallow carbonization, which solves the problem that cloth-brokens are difficult to break to small size, realizes an efficient grinding process and high-quality powder finished products, and promotes the industrial recycling of cloth-broken samples.

CN119845773AActive Publication Date: 2025-04-18WUHAN INST OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411900238.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to further break the cloth to a size below the millimeter level, resulting in difficult problems in the recycling process of the cloth sample.

Method used

The appropriate carbonization temperature is determined by detection and analysis methods, and low temperature shallow carbonization is performed at this temperature, thereby improving the Hastello abrasive index of the cloth-breaking sample, thereby reducing the difficulty of it being ground into powder.

Benefits of technology

It realizes effective carbonization of cloth-breaking samples, reduces energy consumption during grinding, and improves sample powdering properties. It is suitable as a raw material for fluidized bed boilers or airflow-bed gasification furnaces, and promotes the industrial recycling and treatment of cloth-breaking samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845773A_ABST
    Figure CN119845773A_ABST
Patent Text Reader

Abstract

The invention relates to a detection and analysis method for broken cloth. The detection and analysis method comprises the following steps: S1, obtaining the weight W1, volatile component content V1 and component element content of a broken cloth sample; s2, obtaining a thermogravimetric analysis curve and a calorific value Q1 of the broken cloth sample, and a peak temperature T1 of the thermogravimetric analysis curve; s3, carrying out a first carbonization experiment; s4, carrying out a second carbonization experiment to obtain a weight W2; obtaining the content of component elements, the content V2 of volatile components and the calorific value Q2; s5, comparing changes before and after the cloth breaking sample is carbonized, and taking the corresponding carbonization temperature as the screening temperature when the conditions that (W1-W2) / W1 is larger than or equal to 10% and smaller than or equal to 17%, (V1-V2) / V1 is smaller than or equal to 10% and (Q1-Q2) / Q1 is smaller than or equal to 10% are met; and S6, the screening temperature is rechecked. According to the method, the appropriate low-temperature shallow carbonization temperature can be rapidly screened out, so that the weight loss rate of the cloth broken sample treated at the screening temperature is 12-15% and belongs to a normal low range, the calorific value retention rate of the raw material is about 90%, the calorific value of the treated raw material is kept at a relatively high level, and meanwhile, the treated raw material has relatively high grindability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cloth scrap recycling technology, in particular to a cloth scrap detection and analysis method. Background Art

[0002] Cloth scraps are common waste in textile processing and daily life. They are fragments of cloth formed due to the need for cutting. They are usually long strips or irregular blocks of different sizes. Recycling cloth scraps is conducive to the reuse of resources and sustainable development of the environment.

[0003] At present, the main recycling methods are: physical recycling method, chemical recycling method and energy recovery method. Among them, the physical recycling method refers to further crushing the cloth scraps and converting them into small pieces or granules. The crushed cloth scraps can be used to make recycled fibers, filling materials or as other industrial raw materials. The chemical recycling method is mainly used to process synthetic fiber cloth scraps. The polymers in the cloth scraps are depolymerized by chemical methods, and then repolymerized and spun to obtain monomers, and then new fibers are made. However, this method has a complicated process and requires the addition of many chemical solvents and chemicals, and the recycling cost is relatively high. The energy recovery method refers to converting the cloth scraps into products with a certain calorific value after combustion, gasification and other treatments. For example, the heat energy generated by its incineration is converted into electrical energy, or RDF fuel rods are made through an RDF preparation machine.

[0004] Most of the above-mentioned methods for recycling cloth scraps require that the sample to be processed has a uniform texture, which not only refers to the uniform composition of the cloth scraps, but also includes the uniform size, preferably a uniform smaller size, for further processing. For example, patent application CN118256283A discloses a system and method for treating domestic waste, including a pretreatment unit for pretreating the waste to obtain waste particles, mainly by crushing the waste by a shearing crusher, and the particle size of the obtained waste particles is required to be less than 1.5 mm.

[0005] It can be seen that before gasification, the samples to be processed are preferably granular or powdery materials to ensure a high degree of gasification. However, due to the softness of the fabric itself and the fact that most of the fabrics are entangled with each other, the actual crushing effect is not ideal, the time cycle is long, and the energy consumption is high. Summary of the invention

[0006] The purpose of the present invention is to overcome the difficulties in further crushing the existing cloth scraps to a size below millimeters, and to provide a method for detecting and analyzing cloth scraps. The appropriate carbonization temperature of the cloth scrap sample is determined through the detection and analysis process, and then low-temperature shallow carbonization is carried out at the optimal temperature to improve the Hastelloy grindability index of the cloth scrap sample, thereby reducing the difficulty of grinding the cloth scrap sample into powder.

[0007] The specific solution is as follows:

[0008] A method for detecting and analyzing cloth scraps, comprising the following steps:

[0009] S1. Evenly divide the cloth scrap sample to be detected into 4 identical parts, numbered 1#, 2#, 3#, and 4#. Take the 1# cloth scrap sample to be detected for industrial analysis and elemental analysis to obtain the weight W1, volatile content V1, and content of constituent elements of the cloth scrap sample;

[0010] S2. Take the 2# cloth scrap sample to be detected for thermogravimetric analysis to obtain the thermogravimetric analysis curve and calorific value Q1 of the cloth scrap sample, and the peak temperature T1 of the thermogravimetric analysis curve;

[0011] S3. Take the 3# cloth scrap sample to be detected, use T1-X as the starting temperature, T1-Y as the ending temperature, and t1 as the temperature interval, where Y < X < T1 and 5°C < t1 < 20°C, conduct the first carbonization experiment. Observe the appearance of the cloth scrap sample during the carbonization process. The carbonization temperature corresponding to when the appearance of the cloth scrap sample starts to change is recorded as T2, and the carbonization temperature corresponding to when the cloth scrap sample turns black is recorded as T3;

[0012] S4. Take the 4# cloth scrap sample to be detected, use T2 as the starting temperature, T3 as the ending temperature, and t2 as the temperature interval, where t2 < t1, conduct the second carbonization experiment, and test the cloth scrap samples treated at different carbonization temperatures to obtain the weight W2; obtain the content of constituent elements, volatile content V2, and calorific value Q2;

[0013] S5. Compare the changes in the cloth scrap sample before and after carbonization. When 10% ≤ (W1 - W2) / W1 ≤ 17%, (V1 - V2) / V1 ≤ 10%, and (Q1 - Q2) / Q1 ≤ 10%, the corresponding carbonization temperature is used as the screening temperature;

[0014] S6. Recheck the screening temperature, and test the Hardgrove grindability index HGI of the cloth scrap sample. If 50 ≤ HGI ≤ 100, the recheck is passed; otherwise, repeat S1 to S6 until the recheck is passed.

[0015] Further, the industrial analysis in S1 includes the volatile content on a dry basis. Preferably, it also includes at least one of the moisture content on an air-dried basis, the volatile content on an air-dried basis, the ash content on an air-dried basis, the volatile content on a dry basis, the ash content on a dry basis, the volatile content on a dry ash-free basis, and the fixed carbon content.

[0016] Further, the elemental analysis in S1 includes carbon content analysis. Preferably, it further includes at least one of nitrogen content analysis, hydrogen content analysis, sulfur content analysis, oxygen content analysis, and chlorine content analysis.

[0017] Further, the thermogravimetric analysis in S2 includes plotting at least one of a TG curve, a DTG curve, and a DSC curve, preferably a DSC curve.

[0018] Further, the peak temperature in S2 is unique, and 300°C ≤ T1 ≤ 350°C.

[0019] Further, if the peak temperature in S2 is not unique, then the maximum peak temperature is taken as the peak temperature T1.

[0020] Further, in S3, Y ≤ 1 / 3(T1) ≤ X ≤ 2 / 3(T1).

[0021] Further, in S3, 8°C ≤ t1 ≤ 15°C, and in S4, 0.1°C < t2 ≤ 7°C. Preferably, 1°C ≤ t2 ≤ 5°C.

[0022] Further, in S5, when 11% ≤ (W1 - W2) / W1 ≤ 15%, (V1 - V2) / V1 ≤ 5%, and (Q1 - Q2) / Q1 ≤ 10%, the corresponding carbonization temperature is used as the screening temperature.

[0023] Further, in S6, if 90 ≤ HGI ≤ 100, then it passes the review.

[0024] Beneficial effects: The method of the present invention can quickly screen out a suitable low-temperature and shallow carbonization temperature, such that the weight loss rate of the shredded cloth sample after being treated at the screened temperature is in the range of 12 - 15%, which belongs to the normal and relatively low range. The calorific value retention rate of the raw material is about 90%, and the calorific value of the treated raw material remains at a relatively high level. At the same time, it has high grindability, small energy consumption during the grinding process, and good powder formation of the sample. It can be used as a raw material for fluidized bed boilers or entrained flow gasifiers, which helps to promote the industrialized recycling treatment of shredded cloth samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the present invention, the drawings will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention and do not limit the present invention.

[0026] Figure 1 It is a photo of a shredded cloth sample provided by Embodiment 2 of the present invention;

[0027] Figure 2 It is a thermogravimetric analysis diagram of a shredded cloth sample provided by Embodiment 2 of the present invention;

[0028] Figure 3This is an appearance diagram of a cloth scrap sample provided in Example 2 of the present invention after carbonization at 240°C;

[0029] Figure 4 This is an appearance diagram of a cloth scrap sample provided in Example 2 of the present invention after carbonization at 250°C;

[0030] Figure 5 This is an appearance diagram of a cloth scrap sample provided in Example 2 of the present invention after carbonization at 255°C;

[0031] Figure 6 This is a photo of a cloth scrap sample provided in Example 3 of the present invention;

[0032] Figure 7 This is a thermogravimetric analysis diagram of a cloth scrap sample provided in Example 3 of the present invention;

[0033] Figure 8 This is an appearance picture of a cloth scrap sample provided in Comparative Example 1 of the present invention after carbonization at 245°C;

[0034] Fig. 9 This is an appearance picture of a cloth scrap sample provided in Comparative Example 2 of the present invention after carbonization at 250°C;

[0035] Fig.10 This is the appearance picture of the cloth scraps sample provided in Comparative Example 3 of the present invention after carbonization at 255°C. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.

[0037] The test methods used below include:

[0038] For industrial analysis methods of cloth scrap samples, please refer to the national standard GB / T 28731-2012 "Industrial Analysis Methods for Solid Biomass Fuels"

[0039] For the element content test method of cloth scraps, please refer to the industry standard CJ / T 96-2013 "General Test Method for Chemical Properties of Domestic Waste"

[0040] Thermogravimetric analysis of the cloth scraps was performed using a thermogravimetric analyzer. The thermogravimetric analysis was tested under continuous heating conditions. The gas atmosphere was air, the heating rate was 10°C / min, and the test temperature range was from room temperature to 350°C.

[0041] The Hardgrove Grindability Index (HGI) is tested using a Hardgrove Grindability Tester. The test method is based on the national standard GB / T 2565-2014 "Method for Determination of Grindability Index of Coal"

[0042] Example 1

[0043] A method for detecting and analyzing cloth scraps comprises the following steps:

[0044] S1. Divide the cloth scraps to be tested into 4 equal parts, numbered 1#, 2#, 3#, and 4#. Take 1# cloth scraps to be tested for industrial analysis and elemental analysis to obtain the weight W1, volatile matter content V1, and content of constituent elements of the cloth scraps.

[0045] The cloth scraps samples are divided into 4 equal parts for the convenience of subsequent use. The cloth scraps samples will change during some analyses, such as thermogravimetric analysis. In order to ensure the consistency of the samples, the 4 cloth scraps samples should have as little difference as possible.

[0046] Industrial analysis mainly includes dry basis volatile matter content, air-dried basis moisture content, air-dried basis volatile matter content, air-dried basis ash content, dry basis volatile matter content, dry basis ash content, dry ash-free basis volatile matter content and fixed carbon content, etc. The physical property parameters of the cloth scraps are obtained through industrial analysis, among which the dry basis volatile matter content is the basis for subsequent calculations, and other indicators can assist in judging the changes of the cloth scraps after carbonization treatment.

[0047] Elemental analysis can be performed using a photometer or atomic absorption spectrometer, and the analysis targets include carbon content analysis. Since the carbon content will be modified during the carbonization process, it is an indicator that needs attention. Other indicators such as nitrogen content, hydrogen content, sulfur content, oxygen content and chlorine content can be used as auxiliary indicators to evaluate the chemical properties of the cloth scraps.

[0048] S2. Take 2# cloth scrap sample to be tested, perform thermogravimetric analysis, and obtain the thermogravimetric analysis curve and calorific value Q1 of the cloth scrap sample, as well as the peak temperature T1 of the thermogravimetric analysis curve.

[0049] Thermogravimetric analysis includes drawing at least one of a TG curve, a DTG curve and a DSC curve, preferably a DSC curve, which can intuitively obtain the peak temperature. Specifically, the focus of the thermogravimetric analysis curve is mainly the point at which the sample weight begins to change, and the rate of this change. The inflection point on the curve (i.e., the peak) is usually of research significance. When multiple peaks appear, the maximum temperature inflection point is used as the peak temperature, so that the subsequent steps can quickly find the appropriate screening temperature and pass the review.

[0050] S3. Take the 3# cloth fragment sample to be tested, with T1-X as the starting temperature, T1-Y as the ending temperature, and t1 as the temperature interval, where Y < X < T1 and 5°C < t1 < 20°C, and conduct the first carbonization experiment. Observe the appearance of the cloth fragment sample during the carbonization process. The carbonization temperature corresponding to when the appearance of the cloth fragment sample starts to change is denoted as T2, and the carbonization temperature corresponding to when the cloth fragment sample turns black is denoted as T3.

[0051] To save testing time, appropriate starting temperature, ending temperature, and temperature interval are very important. The temperature interval in this embodiment refers to the temperature range from the starting temperature to the ending temperature during heating, which is divided into multiple test nodes, and the temperature difference between adjacent nodes. If the interval is too large, although there are fewer test nodes, the optimal screening temperature may be missed, leading to a repeated analysis process; if the interval is too small, there may be too many test nodes, causing unnecessary waste. Considering the test accuracy and time saving comprehensively, in the preferred solution, Y ≤ 1 / 3(T1) ≤ X ≤ 2 / 3(T1).

[0052] S4. Take the 4# cloth fragment sample to be tested, with T2 as the starting temperature, T3 as the ending temperature, and t2 as the temperature interval, where t2 < t1, and conduct the second carbonization experiment. Test the cloth fragment samples treated at different carbonization temperatures to obtain the weight W2; obtain the content of constituent elements, volatile content V2, and calorific value Q2.

[0053] In the preferred solution, 8°C ≤ t1 ≤ 15°C, and 0.1°C < t2 ≤ 7°C to obtain the best test accuracy.

[0054] S5. Compare the changes in the cloth fragment sample before and after carbonization. When 10% ≤ (W1 - W2) / W1 ≤ 17%, (V1 - V2) / V1 ≤ 10%, and (Q1 - Q2) / Q1 ≤ 10%, the corresponding carbonization temperature is used as the screening temperature;

[0055] S6. Recheck the screening temperature and test the Hardgrove grindability index HGI of the cloth fragment sample. If 50 ≤ HGI ≤ 100, the recheck is passed; otherwise, repeat S1 to S6 until the recheck is passed.

[0056] Example 2

[0057] This example demonstrates the detection and analysis method of the cloth fragments in Example 1 through a specific sample analysis process.

[0058] Conduct a physicochemical property analysis on the cloth fragment sample. The sample (see Figure 1 ) mainly consists of broken cloth heads, a small amount of plastic, and shredded paper, and contains a small amount of dust.

[0059] The proximate analysis of the cloth fragment sample is shown in Table 1.

[0060] Table 1 Industrial analysis of cloth scraps samples of Example 2

[0061]

[0062]

[0063] The elemental analysis results of the cloth scrap raw material samples are shown in Table 2.

[0064] Table 2 Elemental analysis of cloth scraps sample of Example 2 (dry basis)

[0065]

[0066] Thermogravimetric analysis of cloth scraps Figure 2 As shown. Thermogravimetric analysis was tested under continuous temperature increase conditions, the gas atmosphere was air, and the test temperature range was from room temperature to 350°C. The sample began to lose weight due to thermal volatilization at around 200°C. After 250°C, the volatilization accelerated, causing the weight loss rate to increase until an inflection point appeared at around 330°C, and the weight loss rate began to decrease. When the temperature rose to 350°C, the weight loss of the sample was 27.51%.

[0067] The calorific value analysis results of the cloth scrap sample are shown in Table 3. The calorific value of the sample is relatively high, about 22.2MJ / kg. Taking the calorific value of coal and biomass as a reference, the calorific value of standard coal is 29.3MJ / kg; the calorific value of biomass is between 13 and 22MJ / kg. The calorific value of the cloth scrap sample is about 35% higher than the average calorific value of biomass generally accepted.

[0068] Table 3 Calorific value analysis of cloth scraps sample of Example 2

[0069]

[0070] The low-temperature shallow carbonization treatment is carried out in an inert atmosphere (such as nitrogen) using a tubular heating furnace, and the carbonization time is set to 1 hour. Taking the thermogravimetric analysis results as a reference, the low-temperature shallow carbonization temperature starts from 200°C to 280°C, first with 10°C as the temperature interval, and after finding the key treatment temperature range, with 5°C as the temperature interval.

[0071] The experiment found that when the sample was treated at a temperature range of 200-230℃, the appearance of the cloth pieces changed little, and the initial shredding showed strong toughness. Therefore, it is impossible to achieve reasonable grindability by low-temperature shallow carbonization of the cloth pieces at a temperature below 230℃. When the shallow carbonization temperature is greater than 260℃, the cloth pieces turn black. Therefore, the reasonable low-temperature shallow carbonization temperature range should be between 240 and 260℃.

[0072] Example 2 The samples were lightly carbonized at 240, 245, and 250°C, respectively, and the carbonization time was set to 1 hour. The appearance of the samples was as follows: Figure 3 , Figure 4 and Figure 5 As shown in the figure, it can be seen that after carbonization at 245°C, the overall color of the cloth pieces darkened, and the color became even darker at 250°C.

[0073] During the low-temperature shallow carbonization process, the fibers of the sample are damaged by heat and broken, and some volatile substances are also lost. In principle, it is hoped that low-temperature shallow carbonization can improve the grindability index while minimizing the weight loss of the sample.

[0074] The weight loss of the cloth scraps after low-temperature shallow carbonization is shown in Table 4. It can be seen that when the treatment temperature is controlled at less than 245°C, the weight loss of the sample can be controlled within about 15%. Compared with biomass, such a weight loss is within a reasonable and low range.

[0075] Table 4 Weight loss rate of cloth scraps sample after low temperature shallow carbonization in Example 2

[0076]

[0077] The elemental analysis of the samples is shown in Table 5. Overall, compared with the original cloth pieces, the carbon content increased and the oxygen content decreased after low-temperature shallow carbonization.

[0078] Table 5 Elemental analysis of samples after low temperature shallow carbonization in Example 2

[0079]

[0080] The volatile matter and calorific value of the sample after shallow carbonization are shown in Table 6. The calorific value of the raw material after low-temperature shallow carbonization is lower than that before treatment. This is because the light components are volatilized, and the light components usually have relatively high calorific values, resulting in a decrease in the calorific value per unit weight, but the decrease is not large. At the treatment temperatures of 245℃ and 250℃, the calorific value loss per unit weight of the sample is about 10%, and the calorific value of the cloth after low-temperature shallow carbonization is about 20-21MJ / kg, which is about 90% of the calorific value of the raw material.

[0081] Table 6 Volatile matter and calorific value of cloth scraps after low temperature shallow carbonization in Example 2

[0082]

[0083]

[0084] The grindability index of the sample of Example 2 after shallow carbonization is shown in Table 7. The Hardgrove Grindability Index (HGI) is an important parameter for measuring the difficulty of grinding a solid into powder and for evaluating the energy consumption of a mill. The higher the HGI index, the higher the grindability of the material. It can be seen that the grindability index of the cloth scrap sample is very sensitive to the treatment temperature. In this embodiment, the cloth scrap of the sample after carbonization treatment at 245°C can reach a Hardgrove Grindability Index of about 65, and the Hardgrove Grindability Index can reach 95 after treatment at 250°C.

[0085] Table 7 Grindability index of Example 2 after shallow carbonization treatment

[0086]

[0087] Example 3

[0088] This example demonstrates the cloth scraps detection and analysis method in Example 1 through a specific sample analysis process.

[0089] The cloth scraps were analyzed for physical and chemical properties. Figure 6 ) is different from Example 2, in which the sample is mainly composed of broken cloth pieces and a small amount of plastic and shredded paper, and contains a small amount of dust. The sample of Example 3 is mainly composed of various cloth strips, with very little dust.

[0090] The physicochemical properties of the samples in Example 3 are shown in the table below.

[0091] Table 8 Industrial analysis of cloth scraps samples of Example 3

[0092]

[0093] The elemental analysis results of the cloth scrap raw material samples are shown in the table.

[0094] Table 9 Elemental analysis of cloth scraps sample of Example 3 (dry basis)

[0095]

[0096]

[0097] Thermogravimetric analysis of cloth scraps Figure 7 As shown. Thermogravimetric analysis was tested under continuous heating conditions, the gas atmosphere was air, and the test temperature range was from room temperature to 350°C. The sample began to volatilize significantly at around 230°C, and began to volatilize rapidly at around 275°C, and the volatilization slowed down significantly at around 310°C. At 350°C, the sample only lost 11.06% of its weight. Overall, the processing temperature required for the sample in this embodiment should be higher than that in Example 2, but the weight loss during the heat treatment process is much lower than that in Example 2.

[0098] The calorific value analysis results of the cloth scraps are shown in the table below. The calorific value of the sample is relatively high, about 24.2MJ / kg.

[0099] Table 10 Calorific value analysis of cloth scraps sample of Example 3

[0100]

[0101] The low-temperature shallow carbonization treatment is carried out in an inert atmosphere (such as nitrogen) using a tubular heating furnace, and the carbonization time is set to 1 hour. Taking the thermogravimetric analysis results as a reference, the low-temperature shallow carbonization temperature starts from 200°C to 280°C, first with 10°C as the temperature interval, and after finding the key treatment temperature range, with 5°C as the temperature interval.

[0102] The experiment found that when the sample was treated at a temperature range of 200-230℃, the appearance of the cloth pieces changed little, and the initial shredding showed strong toughness. Therefore, it is impossible to achieve reasonable grindability by low-temperature shallow carbonization of the cloth pieces at a temperature below 230℃. When the shallow carbonization temperature is greater than 260℃, the cloth pieces turn black. Therefore, the reasonable low-temperature shallow carbonization temperature range should be between 245 and 260℃.

[0103] Example 3 The samples were lightly carbonized at 245, 250, and 255°C, respectively, and the carbonization time was set to 1 hour. The appearance of the samples was as follows: Figure 8 , Fig. 9 and Fig.10 As shown in the figure, it can be seen that as the carbonization temperature increases, the overall color of the cloth pieces gradually deepens.

[0104] During the low-temperature shallow carbonization process, the fibers of the sample are damaged by heat and broken, and some volatile substances are also lost. In principle, it is hoped that low-temperature shallow carbonization can improve the grindability index while minimizing the weight loss of the sample.

[0105] The weight loss of the cloth scraps after low-temperature shallow carbonization is shown in the table below. Compared with biomass, the weight loss of the samples is within a reasonable and low range.

[0106] Table 11 Weight loss rate of cloth scraps sample after low temperature shallow carbonization in Example 3

[0107]

[0108] The elemental analysis of the samples is shown in the following table. Overall, compared with the original cloth pieces, the carbon content increased and the oxygen content decreased after low-temperature shallow carbonization.

[0109] Table 12 Elemental analysis of samples after low temperature shallow carbonization in Example 3

[0110]

[0111] The volatile matter and calorific value of the sample after shallow carbonization are shown in the following table. The calorific value of the raw material after low-temperature shallow carbonization is lower than that before treatment. This is because the light components are volatilized, and the light components usually have a relatively high calorific value, resulting in a decrease in the calorific value per unit weight, but the decrease is not large.

[0112] Table 13 Volatile matter and calorific value of cloth scraps after low temperature shallow carbonization in Example 3

[0113]

[0114] The grindability index of the sample in Example 2 after shallow carbonization is shown in the following table.

[0115] Table 14 Grindability index of Example 3 after shallow carbonization treatment

[0116]

[0117] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0118] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0119] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for detecting and analyzing cloth scraps, characterized in that: It includes the following steps: S1. Evenly divide the cloth fragment sample to be detected into 4 identical parts, numbered 1#, 2#, 3#, and 4#. Take the 1# cloth fragment sample to be detected for industrial analysis and elemental analysis to obtain the weight W1, volatile content V1, and the content of constituent elements of the cloth fragment sample; S2. Take the 2# cloth fragment sample to be detected for thermogravimetric analysis to obtain the thermogravimetric analysis curve and calorific value Q1 of the cloth fragment sample, and the peak temperature T1 of the thermogravimetric analysis curve; S3. Take the 3# cloth fragment sample to be detected, with T1 - X as the starting temperature, T1 - Y as the ending temperature, and t1 as the temperature interval, where Y < X < T1 and 5°C < t1 < 20°C, conduct the first carbonization experiment. Observe the appearance of the cloth fragment sample during the carbonization process. The carbonization temperature corresponding to when the appearance of the cloth fragment sample starts to change is denoted as T2, and the carbonization temperature corresponding to when the cloth fragment sample turns black is denoted as T3; S4. Take the 4# cloth fragment sample to be detected, with T2 as the starting temperature, T3 as the ending temperature, and t2 as the temperature interval, where t2 < t1, conduct the second carbonization experiment. Test the cloth fragment samples treated at different carbonization temperatures to obtain the weight W2; obtain the content of constituent elements, volatile content V2, and calorific value Q2; S5. Compare the changes in the cloth fragment sample before and after carbonization. When 10% ≤ (W1 - W2) / W1 ≤ 17%, (V1 - V2) / V1 ≤ 10%, and (Q1 - Q2) / Q1 ≤ 10%, the corresponding carbonization temperature is used as the screening temperature; S6. Recheck the screening temperature, test the Hardgrove grindability index HGI of the cloth fragment sample. If 50 ≤ HGI ≤ 100, it passes the recheck; otherwise, repeat S1 to S6 until it passes the recheck.

2. The method for detecting and analyzing cloth scraps according to claim 1, characterized in that: The industrial analysis in S1 includes the volatile content on a dry basis. Preferably, it also includes at least one of the moisture content on an air - dry basis, volatile content on an air - dry basis, ash content on an air - dry basis, volatile content on a dry basis, ash content on a dry basis, volatile content on a dry ash - free basis, and fixed - carbon content.

3. The cloth scraps detection and analysis method according to claim 1 or 2, characterized in that: The elemental analysis in S1 includes carbon - content analysis. Preferably, it also includes at least one of nitrogen - content analysis, hydrogen - content analysis, sulfur - content analysis, oxygen - content analysis, and chlorine - content analysis.

4. The method for detecting and analyzing cloth scraps according to claim 1, characterized in that: The thermogravimetric analysis in S2 includes plotting at least one of the TG curve, DTG curve, and DSC curve, preferably the DSC curve.

5. The method for detecting and analyzing cloth scraps according to claim 4, characterized in that: The peak temperature in S2 is unique, and 300°C ≤ T1 ≤ 350°C.

6. The method for detecting and analyzing cloth scraps according to claim 4, characterized in that: If the peak temperature in S2 is not unique, then take the maximum peak temperature as the peak temperature T1.

7. The cloth scraps detection and analysis method according to claim 5 or 6, characterized in that: In S3, Y ≤ 1 / 3(T1) ≤ X ≤ 2 / 3(T1).

8. The method for detecting and analyzing cloth scraps according to claim 7, characterized in that: In S3, 8°C ≤ t1 ≤ 15°C, and in S4, 0.1°C < t2 ≤ 7°C. Preferably, 1°C ≤ t2 ≤ 5°C.

9. The method for detecting and analyzing cloth scraps according to claim 1, characterized in that: In S5, when 11% ≤ (W1 - W2) / W1 ≤ 15%, (V1 - V2) / V1 ≤ 5%, and (Q1 - Q2) / Q1 ≤ 10%, the corresponding carbonization temperature is used as the screening temperature.

10. The method for detecting and analyzing cloth scraps according to claim 9, characterized in that: In S6, if 90 ≤ HGI ≤ 100, it passes the recheck.

Citation Information

Patent Citations

  • Household garbage treatment system and treatment method

    CN118256283A

  • Method for production of carbonized cloth, and carbonized cloth produced by the method

    CN101506415A

  • Thermogravimetric analysis method for gadolinium content in gadolinium contrast agent

    CN111751241A

  • Carbon fiber ash content determination method

    CN116106164A

  • Method for analyzing carbon composite material, carbon fiber composite material and evaluation method of carbon material for secondary battery

    JP2018091749A